Development, Civil Society and Faith-Based Organizations
XX, 279 p.
Keywords: This book examines the role of faith-based organizations in managing international aid, providing services, defending human rights and protecting democracy. It argues that greater engagement with faith communities and organizations is needed, and questions traditional secularism that has underpinned development policy and practice in the North.